2015
DOI: 10.1371/journal.pone.0112217
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Barcoding in Pencilfishes (Lebiasinidae: Nannostomus) Reveals Cryptic Diversity across the Brazilian Amazon

Abstract: Nannostomus is comprised of 20 species. Popularly known as pencilfishes the vast majority of these species lives in the flooded forests of the Amazon basin and are popular in the ornamental trade. Among the lebiasinids, it is the only genus to have undergone more than one taxonomic revision. Even so, it still possesses poorly defined species. Here, we report the results of an application of DNA barcoding to the identification of pencilfishes and highlight the deeply divergent clades within four nominal species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 53 publications
2
38
0
1
Order By: Relevance
“…Genetic distance results from the mtDNA COI sequences indicate very high pairwise values among the analysed species groups of Characidium , except with respect to comparisons among populations of C. zebra (below 0.02). Numerous studies of characiform fishes have demonstrated high interspecific genetic distances using mtDNA, as for example in curimatids (Melo, Ochoa, Vari, & Oliveira, ), lebiasinids (Benzaquem, Oliveira, Silva Batista, Zuanon, & Porto, ), parodontids (Bellafronte, Mariguela, Pereira, Oliveira, & Moreira‐Filho, ), bryconids (Machado, Ishizuka, Freitas, Valiati, & Galetti, ) and characids (Melo et al, ; Silva, Melo, Oliveira, & Benine, ). Because nucleotide substitutions accumulate through time (i.e., older clades tend to accumulate more substitutions), it is likely that high distance values result from the old splitting of the most recent common ancestor of Characidium from other crenuchids during the Paleogene (Poveda‐Martínez et al, ), a relatively old timing for genus‐level cladogenesis in Neotropical fishes (López‐Fernández & Albert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic distance results from the mtDNA COI sequences indicate very high pairwise values among the analysed species groups of Characidium , except with respect to comparisons among populations of C. zebra (below 0.02). Numerous studies of characiform fishes have demonstrated high interspecific genetic distances using mtDNA, as for example in curimatids (Melo, Ochoa, Vari, & Oliveira, ), lebiasinids (Benzaquem, Oliveira, Silva Batista, Zuanon, & Porto, ), parodontids (Bellafronte, Mariguela, Pereira, Oliveira, & Moreira‐Filho, ), bryconids (Machado, Ishizuka, Freitas, Valiati, & Galetti, ) and characids (Melo et al, ; Silva, Melo, Oliveira, & Benine, ). Because nucleotide substitutions accumulate through time (i.e., older clades tend to accumulate more substitutions), it is likely that high distance values result from the old splitting of the most recent common ancestor of Characidium from other crenuchids during the Paleogene (Poveda‐Martínez et al, ), a relatively old timing for genus‐level cladogenesis in Neotropical fishes (López‐Fernández & Albert, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of this species in Mundaú river basin in Ceará State is the northern and westernmost record in MNCE, and it could be a relictual distribution and another evidence of the preterit connection between the Neotropical forested biomes. Currently, N. beckfordi is considered a poorly defined species complex, which needs a taxonomic review (Benzaquem et al 2015). The native or introduced status of this taxon needs to be addressed once endemic undescribed species could be unprotected.…”
Section: Discussionmentioning
confidence: 99%
“…The most widespread molecular method used in taxonomy has been the DNA barcoding, which consists on the use of a single gene from mitochondrial DNA (cytochrome oxidase subunit I – COI) as a proxy for species differentiation (Hebert et al 2003). In fact, several studies have been carried out using molecular markers and new species have been delimited and/or described, in most cases, based both on molecular and morphological evidence (e.g., Costa and Amorim 2011, Costa et al 2012, Roxo et al 2012, Villa-Verde et al 2012, Castro-Paz et al 2014, Costa et al 2014, Benzaquem et al 2015, Mattos et al 2015, Costa et al 2017). …”
Section: Introductionmentioning
confidence: 99%